(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
This paper examines the impact of teacher feedback on the development of students’ speaking skills in second and foreign language classrooms. Speaking is widely regarded as one of the most challenging and anxiety-provoking skills to acquire, and the quality, timing, and type of feedback teachers provide can substantially influence learners’ fluency, accuracy, confidence, and willingness to communicate. Drawing on second language acquisition theory and classroom-based research, this paper reviews the major forms of oral feedback, including explicit correction, recasts, elicitation, clarification requests, and metalinguistic feedback, and considers how each interacts with learner affect and motivation. The paper further discusses the balance between corrective and affective feedback, the role of feedback timing, and the importance of individualized, learner-centered approaches. Findings across the literature suggest that feedback which is consistent, specific, and delivered within a supportive classroom climate produces the strongest gains in oral proficiency, while feedback perceived as overly critical or poorly timed can increase anxiety and reduce participation. The paper concludes with pedagogical recommendations for teachers seeking to use feedback as a tool for sustained oral language development.